Business Process Monitoring with S-BPM - Schmidt, Werner; Fleischmann, Albert (S-BPM ONE - Running Processes, 2013)
Business Process Monitoring plays an important role in organizational development. It delivers management information and thus allows for better decision making in terms of process design, implementation and execution. This contribution first sheds some light on the importance and forms of business process monitoring. Then we look at current monitoring features of S-BPM software supporting the S-BPM approach and discuss development perspectives particularly in the field of Business Activity Monitoring (BAM). In this context we adapt an existing concept for modeling BAM specifications with reference to BPMN models for the use with S-BPM.